IL-25 and type 2 innate lymphoid cells induce pulmonary fibrosis. - SAUNDERS, SEAN; FALLON, PADRAIC; DONNELLY, SEAMAS (My University, 2014)
Disease conditions associated with pulmonary fibrosis are progressive and have a poor long-term prognosis with irreversible changes in airway architecture leading to marked morbidity and mortalities. Using murine models we demonstrate a role for interleukin (IL)-25 in the generation of pulmonary fibrosis. Mechanistically, we identify IL-13 release from type 2 innate lymphoid cells (ILC2) as sufficient to drive collagen deposition in the lungs of challenged mice and suggest this as a potential mechanism through which IL-25 is acting. Additionally, we demonstrate that in human idiopathic pulmonary fibrosis there is increased pulmonary expression of IL-25 and also observe a population ILC2 in the lungs of idiopathic pulmonary fibrosis patients. Collectively, we present an innate mechanism for the generation of pulmonary fibrosis, via IL-25 and ILC2, that occurs independently of T-cell-mediated antigen-specific immune responses. These results suggest the potential of therapeutically targeting IL-25 and ILC2 for the treatment of human fibrotic diseases.
PUBLISHED
Keywords: therapy; innate response; inflammation; cytokine; Immunology, Inflammation & Infection; Biomedical sciences